Histoire de la Côte-des-Neiges. Les premiers artisans - Rousseau, Sylvain (2025)
Keywords: Artisans

Agathe de Saint-Père. Entrepreneure en Nouvelle-France - Forget, Nicolle (Septentrion, 2024)
Keywords: Saint-Père, Agathe de

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

L’importance des métaux dans une ville naissante : les artisans du métal dans l’espace social et urbain de Montréal de 1642 à 1701 - Blouin, Sonia (Université de Sherbrooke, 2021)
Keywords: Artisans; Fer et acier; Travail

Les céramiques et les réseaux maritimes du fort de Ville-Marie, Montréal, 1642-1688 - Bourgela, Samuel (Université de Montréal, 2018)
Keywords: Marchands; Port; Poterie

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Au chant des ailes des moulins - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Meunerie

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

Le moulin de Pointe-Claire, 1710-2010 / 1710-2010, The Pointe-Claire Mill - Arsenault, Claude (Société pour la sauvegarde du patrimoine de Pointe-Claire, 2010)
Keywords: Meunerie; Pointe-Claire

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

De couturière à Soeur Grise. Le parcours inhabituel de Marie Catherine Demers Dessermon dans le Montréal du XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2009)
Keywords: Communautés religieuses; Confection; Soeurs Grises

Les entreprises d'imprimerie et d'édition en Amérique du Nord britannique, 1751-1840 - Hare, John; Wallot, Jean-Pierre (Mens, 2005)
Keywords: Imprimerie; Édition

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Patrimoine archéologique de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

Le grain, la meule et les vents: le métier de meunier en Nouvelle-France - Laperle, Dominique (GID, 2003)
Keywords: Meunerie

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

Les techniques et le commerce de la tannerie à Montréal au XVIIIe siècle - Perrier, Jocelyne (Scientia Canadensis, 2000)
Keywords: Artisans; Marchands; Tannerie

De la paysanne au tisserand: la production textile dans la région de Montréal au XVIIIe siècle - Roy, Emmanuelle (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 1999)
Keywords: Artisans; Textile; Tissus

Les boulangers à Montréal, de la fondation à 1750. Étude d'histoire socio-économique - Lamonde, Robert (Université de Montréal, 1997)
Keywords: Alimentation; Boulangerie

Familles de charpentiers et de menuisiers à Montréal au XVIIIe siècle: alliances matrimoniales et reproduction sociale - Langlois, France-Isabelle (Université de Montréal, 1997)
Keywords: Charpentiers; Famille; Mariage; Menuisiers

Les familles de tisserands de la plaine de Montréal au XVIIIe siècle: étude socioprofessionnelle - Roy, Emmanuelle (Université de Montréal, 1997)
Keywords: Artisans; Textile; Tissus

Les meuniers dans la région de Montréal à l'époque de la Nouvelle-France (1642-1760): alliances matrimoniales et reproduction sociale - Laperle, Dominique (Université de Montréal, 1996)
Keywords: Famille; Mariage; Meunerie

Fouilles archéologiques, 1994. Site Logan-Munn, BiFj-25 et BiFj-4. Angle des rues McGill et de la Commune, Vieux-Montréal. Volume 1: Rapport - Ethnoscop (Société immobilière du patrimoine architectural de Montréal (SIMPA), Ville de Montréal et Ministère de la Culture et des Communications, 1995)
Keywords: Construction navale; Hôpital Général

Structure et effectifs des métiers du fer à Montréal avant 1765 - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1995)
Keywords: Artisans; Fer et acier

Moulins et meuniers du Bas-Lachine, 1667-1890 - Gravel, Denis (Les Cahiers du Septentrion, 1995)
Keywords: Arrondissements; LaSalle; Lachine; Meunerie

La culture matérielle des Canadiens au XVIIIe siècle: analyse du niveau de vie des artisans du fer - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1994)
Keywords: Artisans; Fer et acier

Le niveau de vie des artisans du fer à Montréal et à Québec entre 1730 et 1780 - Bouchard, Dominique (Université de Montréal, 1992)
Keywords: Artisans; Fer et acier

Vivre en Canada - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

Moulin à vent - Bélisle, Jean (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Meunerie; Patrimoine; Pointe-aux-Trembles

Moulin banal de Pointe-Claire - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Meunerie; Patrimoine; Pointe-Claire

Les Sicard - Bertrand, Jacques (Cahiers d'histoire du Sault-au-Récollet, 1990)
Keywords: Meunerie; Rivière-des-Prairies

DULONGPRÉ, LOUIS - Bazin, Jules (Dictionnaire biographique du Canada, 1988)

GIBB, BENAIAH - Burgess, Joanne (Dictionnaire biographique du Canada, 1987)

QUÉVILLON, LOUIS - Cloutier, Nicole (Dictionnaire biographique du Canada, 1987)

DUVAL, CHARLES - Derome, Robert (Dictionnaire biographique du Canada, 1987)

ROUSSEAU, DOMINIQUE - Derome, Robert (Dictionnaire biographique du Canada, 1987)

McCORD, THOMAS - Kyte Senior, Elionor (Dictionnaire biographique du Canada, 1987)

GRAY, JOHN - Miller, Carman (Dictionnaire biographique du Canada, 1987)

Extrait de la vie domestique d'une famille de cultivateur et d'artisan du faubourg Saint-Louis, 1745-1825, site Viger, Montréal - Laliberté, Monique (Société d'archéologie et de numismatique de Montréal, 1986)
Keywords: Artisans; Famille; Faubourgs; Quartiers; Saint-Louis

La boulangerie à Montréal sous le régime français - Montbriand, Monique (Cahier de la Société historique de Montréal, 1985)
Keywords: Boulangerie

FISHER, DUNCAN - Armstrong, Frederick H. (Dictionnaire biographique du Canada, 1983)

ROLLO, JAMES - Collard, Elizabeth (Dictionnaire biographique du Canada, 1983)

CRUICKSHANK, ROBERT - Derome, Robert (Dictionnaire biographique du Canada, 1983)

HUGUET, Latour, PIERRE - Derome, Robert; Morgan, Norman (Dictionnaire biographique du Canada, 1983)

VIGER, DENIS - Désy, Louise (Dictionnaire biographique du Canada, 1983)

EDWARDS, EDWARD - Hare, John E. (Dictionnaire biographique du Canada, 1983)

PÉRINAULT, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

Les meuniers dans la seigneurie de l'Ile de Montréal au XVIIIe siècle - Objois, Catherine (Université de Montréal, 1981)
Keywords: Meunerie; Seigneurie

DELEZENNE, IGNACE-FRANÇOIS - Derome, Robert (Dictionnaire biographique du Canada, 1980)

VARIN, La Pistole, JACQUES - Derome, Robert (Dictionnaire biographique du Canada, 1980)

MESPLET, FLEURY - Galarneau, Claude (Dictionnaire biographique du Canada, 1980)

SOUSTE, ANDRÉ - Lachance, André (Dictionnaire biographique du Canada, 1980)

HUPPÉ, Lagroix, JOSEPH - Moogk, Peter N. (Dictionnaire biographique du Canada, 1980)

TESSIER, Lavigne, PAUL - Moogk, Peter N. (Dictionnaire biographique du Canada, 1980)

Le chauffage domestique au Canada: des origines à l'industrialisation - Moussette, Marcel (Université Laval, 1980)
Keywords: Bois de chauffage

CIRIER, ANTOINE - Porter, John R. (Dictionnaire biographique du Canada, 1980)

FOUREUR, Champagne, LOUIS - Porter, John R. (Dictionnaire biographique du Canada, 1980)

BARSALOU, JEAN-BAPTISTE - Tremblay, Yves-Jean (Dictionnaire biographique du Canada, 1980)

The Ancestor of Quebec's Craft Unions: the Montreal Shoemakers' Protest of 1729 - Moogk, Peter N. (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1978)
Keywords: Artisans; Chaussure; Grèves

CHEVAL, dit Saint-Jacques, Chevalier, JACQUES-JOSEPH - Auger, Roland-J. (Dictionnaire biographique du Canada, 1974)

GADOIS, Mauger, JACQUES - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

JOURDAIN, Labrosse, PAUL-RAYMOND - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

PARADIS, ROLAND - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

SAINT-PÈRE, AGATHE DE - Doyon-Ferland, Madeleine (Dictionnaire biographique du Canada, 1974)

CORON, CHARLES-FRANÇOIS - Kallmann, Helmut (Dictionnaire biographique du Canada, 1974)

MOREAU, EDME - Moogk, Peter N. (Dictionnaire biographique du Canada, 1974)

The Craftsmen of New France - Moogk, Peter N. (Université de Toronto, 1973)
Keywords: Apprentissage; Artisans

BROSSARD, URBAIN - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

CHABOULIÉ (Chaboillez), CHARLES - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

FÉZERET, RENÉ - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

QUESNEVILLE, JEAN - Lahaise, Robert (Dictionnaire biographique du Canada, 1969)

RAIMBAULT, PIERRE - Lahaise, Robert (Dictionnaire biographique du Canada, 1969)

GADOIS, PIERRE - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

PAILLARD, LÉONARD, le Poitevin - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

PAYNE, SAMUEL - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

LE CONTE DUPRÉ, LOUIS - Nish, Cameron (Dictionnaire biographique du Canada, 1969)

PRUD’HOMME, LOUIS - Lefebvre, Jean-Jacques (Dictionnaire biographique du Canada, 1966)

LAUSON, GILLES - Vachon, André (Dictionnaire biographique du Canada, 1966)

Madame de Repentigny - Leland, Marine (Bulletin des recherches historiques, 1954)
Keywords: Saint-Père, Agathe de

Agathe de Saint-Père, Dame Legardeur de Repentigny - Massicotte, E.-Z. (Bulletin des recherches historiques, 1944)
Keywords: Saint-Père, Agathe de

La boulangerie à Montréal avant 1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Keywords: Boulangerie

Le moulin des seigneurs de Montréal - Lapalice, O. (Bulletin des recherches historiques, 1931)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Orfèvres et bijoutiers du Régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Keywords: Bijouterie; Orfèvres

Quelques sculpteurs montréalais sous la domination française - Massicotte, E.-Z. (Bulletin des recherches historiques, 1928)
Keywords: Sculpture

Pierre Prud'homme, un montréalais compagnon de La Salle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1922)
Keywords: Cavelier de La Salle, René-Robert; Prud'homme, Pierre

La Saint-Eloi et la corporation des armuriers à Montréal, au XVIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1917)
Keywords: Armuriers

Pierre Prud'homme, compagnon de La Salle - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1914)
Keywords: Cavelier de La Salle, René-Robert; Prud'homme, Pierre